ELESP GRADUATE TEACHER IDENTITY: WHY SOME CHOSE NON-TEACHING JOB? - Fransiska Wulandari (ELTR Journal, 2020)
This paper investigates English Language Education Study Program (ELESP) graduates’ teacher identity construction. This paper focuses on the reason why ELESP graduates prefer non-teaching job instead of being a teacher. This paper employs qualitative study and focuses deeper on the phenomena. In gathering the data, questionnaire and deep interview was conducted as the research instrument. The result shows that economic reason becomes one factor why ELESP graduate leave the teaching job.